Quality improvement project : reducing non-conformities of the samples for haemostasis testing in a secondary healthcare centre through the nurses' education in phlebotomy - Banković-Radovanović, Patricija (Array, 2020)
Introduction: Poor compliance to the current guidelines and lack of knowledge among nurses about proper blood sampling is set as the study hypothesis. Here is presented a quality improvement project with following aims: a) to identify the most prevalent non-conformity of the samples for haemostasis testing, b) to identify the cause of sample non-conformity, c) to perform corrective action(s) and d) to assess the effectiveness of the corrective action(s). Materials and methods: The rate of non-conformity of samples collected for haemostasis tests was established for hospital wards with inpatients. Phlebotomy practice was audited throughout anonymous questionnaire among hospital’s nurses who perform phlebotomy. Education about blood sampling was performed as a 1-hour lecture in different small groups each working day within one month. Education effectiveness was assessed through the evaluation of sample quality and is considered effective if more than half of the hospital wards significantly reduced their sample non-conformities rate. Results: Clotted sample constituted 84% of sample non-conformities. The questionnaire revealed nurses’ poor knowledge in phlebotomy. There was no difference in nurses’ knowledge regarding the level of education or work experience. Reduction in sample non-conformities was observed in 7 out of 9 wards 4 months after education; this improvement was statistically significant for 5 wards. Conclusion: Clotted sample as the most prevalent non-conformity of the samples for haemostasis testing is caused by the lack of knowledge of the nurses in several parts of the phlebotomy process. Specific education of the motivated personnel in small groups was successful and long-term effective.